Using the life satisfaction approach to value daylight savings time transitions: Evidence from Britain and Germany - Daniel Kuehnle; Christoph Wunder (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2014)
Daylight savings time (DST) represents a public good with costs and benefits. We provide the first comprehensive examination of the welfare effects of the spring and autumn transitions for the UK and Germany. Using individual-level data and a regression discontinuity design, we estimate the effect of the transitions on life satisfaction. Our results show that individuals in both the UK and Germany experience deteriorations in life satisfaction in the first week after the spring transition. We find no effect of the autumn transition. We attribute the negative effect of the spring transition to the reduction in the time endowment and the process of adjusting to the disruption in circadian rhythms. The effects are particularly strong for individuals with young children in the household. We conclude that the higher the shadow price of time, the more difficult is adjustment. Presumably, an increase in flexibility to reallocate time could reduce the welfare loss for individuals with binding time constraints.
Keywords: H41; I31; 330; daylight savings time; life satisfaction; regression discontinuity; UK; Germany